Act of June 13, 1923, ch. 339, § 2, 1923 Cal. Stat. 696 - (:unkn) unknown (General Publisher, 1923)
Prohibited firearm possession and any “ other firearm capable of being concealed upon the person ” for those convicted of a felony or unnaturalized foreign-born.
--
Keywords: POSSESSION - DANGEROUS PERSONS